GLP‐1 induces alpha cell proliferation and overrides leptin suppression induced by negative energy balance in vagotomized rats. Issue 9 (17th April 2019) - Morais, Tiago; Patrício, Barbara; Pereira, Sofia Silva; Andrade, Sara; Carreira, Marcos; Casanueva, Felipe F.; Monteiro, Mariana P.
Abstract: Glucagon‐like peptide‐1 (GLP‐1) influences energy balance by exerting effects on food intake and glucose metabolism, through mechanisms that are partially dependent on the vagal pathway. The aim of this study was to characterize the effects of chronic GLP‐1 stimulation on energy homeostasis and glucose metabolism in the absence of vagal innervation Truncal vagotomized (VGX) and sham operated rats (SHAM) received an intraperitoneal GLP‐1 infusion (3.5 pmol/kg/min) trough mini‐osmotic pumps. To dissect the effects derived from vagal denervation on food intake, an additional group was included consisting of sham operated rats that were PAIR FED to VGX. Food intake and body weight were recorded throughout the experimental period, while the percentage of white and brown adipose tissue, fasting glucose, insulin, gastro‐intestinal hormonal profile, hypothalamic, and BAT gene expression were assessed at endpoint. VGX rats had significantly lower food intake, body weight gain, and leptin levels when compared with SHAM rats. Despite having similar body weight, PAIR‐FED rats had lower fasting leptin, insulin and insulin resistance, while having higher ghrelin levels than VGX. GLP‐1 infusion did not influence food intake or body weight, but was associated with lower leptin levels in VGX and lower pancreatic α‐cells ki‐67 staining in SHAM. Concluding, this study corroborates that the vagus nerve may modulate whole body energy homeostasis by acting in peripheral signals. Our data suggest that in the absence of vagal or parasympathetic tonus, GLP‐1 mediated inhibition of cell proliferation markers in α‐cells is prevented, meanwhile leptin suppression, associated with a negative energy balance, is partially overridden. Abstract : The aim of the present study was to assess the role of the vagus nerve in mediating the influence of chronic glucagon‐like peptide‐1 (GLP‐1) administration on whole body energy homeostasis. For that purpose, we used truncal vagotomized (VGX) and sham operated rats (SHAM) that received an intraperitoneal GLP‐1 infusion (3.5 pm/kg/min) through mini‐osmotic pumps. We also used a PAIR‐FED group to distinguish what could be the effects derived from vagal denervation on food intake and body weight. Our study seems to corroborate that the vagus nerve may modulate whole body energy homeostasis by acting in peripheral signals. Our data suggest that in the absence of vagal or parasympathetic tonus, GLP‐1 mediated inhibition of cell proliferation markers in α‐cells is prevented, meanwhile leptin suppression, associated with a negative energy balance, is partially overridden.